RANCANG BANGUN APLIKASI DATA BUKU DAN TOKO BUKU DENGAN METODE LOCATION-BASED SERVICE BERBASIS ANDROID - Azhar Azhar (Jurnal Real Riset, 2022)
This system is one of the online bookstore system that sells various categories of books, whose products are sourced from several suppliers. Bookstores located in Lhokseumawe have difficulty in disseminating product information. This research focus to Designing Data Book Apps And Bookstores Based on Location Based Service Methods and Android has a problem formula for how to design and build book-logging apps and bookstores. The purpose of this research is to make the app as a product promotion medium for booksellers and to provide nearby bookstore information for people from out of town by using. This research uses location based service methods. The data sources used are primary and secondary data from Google Maps. Based on the testing conducted, it is obtained the conclusion that users of this system do not have to have a physical store to sell books, and for bookstore seekers must enable GPS to locate the starting point to the nearest bookstore location point.Keywords : Bookstores, Location Based Service